Public Forests Under Threat in the Brazilian Amazon: Strategies for Coping Shifts in Environmental Policies and Regulations - Moraes, Iranilda; Azevedo-Ramos, Claudia; Pacheco, Jessica (Frontiers in Forests and Global Change, 2021)
Brazil has 310.5 million hectares of public forests, almost 92% of which in the Amazon. Since the 1980s, Brazilian environmental legislation has been improving and, along with other measures, has contributed to a significant reduction in deforestation in the Amazon since 2005. However, changes in the legal framework and dismantling of successful socio-environmental policies threaten public forests in the Amazon. Here, we highlighted some relevant changes in the legal and political framework and prioritized some actions to safeguard the largest tropical forest in the world considering an adverse political context. We emphasized strategies associated with (1) the institutionalization of practices and processes; and (2) market-driven influence on sustainable production. The purpose is to inhibit current threats until more favorable and participatory circumstances are present and a comprehensive range of past success measures may be revisited.